The Effect of Tax Evasion on the Outcome of Local Collection A Case Study of Laghouat Municipality during the Period 2015-2018 - مجلد, عبد القادر (Finance and Business Economies Review, 2021)
Local collection is a basic resource for local groups (municipality, state, solidarity and guarantee fund for local groups), which generally consists of direct taxes and fees such as fees on professional activity and the only levy tax, indirect taxes and fees as a fee on value added and other taxes and fees such as car vouchers. The income of local collection changes with an increase in the percentage of evaders from paying their dues, which has a negative impact on the income of local groups and thus affects the manage of local development and this is evident through the study of the tax revenues of the municipality of Laghouat, and through tax investigations (accounting investigation, investigation of documents) on the statements of taxpayers. , It was noted that significant amounts resulted from tax evasion.